A photographic memory ; 1968-1989 - Schlesinger, Peter 1948- (Damiani, 2015)
The photographs of artist Peter Schlesinger are a visual diary of an extraordinary life that intersected with some of the brightest names in the worlds of art, fashion, and society. Schlesinger's remarkable journey began in 1966 when as an 18 year old student at UCLA he met the artist David Hockney. The two moved to London, where Schlesinger was introduced to the city's fashionable bohemian society. There, as well as on trips, Schlesinger met and photographed some of the great personalities of the day, including Cecil Beaton, Paloma Picasso, Grace Coddington, Tina Chow, Christopher Isherwood, and Manolo Blahnik - to name just a few. This beautifully produced book presents an overview of 30 years of photographic work from Schlesinger's archives. In addition to intimate portraits, the book includes Schlesinger's evocative still lives, which convey the romance, humour, and elegance of their time. This is the first monograph to present the full range of Schlesinger's photographic work
Keywords: Schlesinger, Peter -- 1948-; Geschichte 1968-1989; Bildband